FORMATION OF COMMUNICATIVE COMPETENCE IN THE TRAINING OF FUTURE ECONOMISTS - Zadorozhna, N. (Continuing Professional Education: Theory and Practice, 2019)
The article attempts to show the necessity of introducing communicative approach in conditions of future economists training that was caused by Europe’s and the world trend of integration and globalization of the world economy; standardization of European education on the principles of the Bologna agreement. That is why the issue of communicative approach in higher education is seen today as the conceptual basis of modern education. The purpose of the article is theoretical justification for the formation of professional competence and in particular communicative competence as a component of professional competence of future specialists of economics. We consider issues of professional competence, the main key professional competence of future specialists in the field of Economics and Business, analyze current approaches to the study of definite phenomenon. In the given article it is also analyzed the necessity of communicative competence as a way of increasing the competitiveness of future professional economists in the labor market. The main attention is given to the interpretation and effect the terms “competence”, “communicative competence “.